IMPROVING SPEAKING SKILL OF SMP BUDI UTAMA KEROBOKAN STUDENTS THROUGH INSIDE OUTSIDE CIRCLE WITH VIDEO - Arsana, Anak Agung Putu; Wirastuti, I Gusti Agung Putri; Serowero, Tesalonika Alexanderina (Suluh Pendidikan : Jurnal Ilmu-Ilmu Pendidikan, 2020)
The study of this research was to figure out the improvement of speaking skill of the eighth grade students of SMP Budi UtamaKerobokan in academic year 2019/2020 through inside outside circle with video. The subjects were the eighth grade students of SMP Budi UtamaKerobokan in academic year 2019/2020. The passing grade of the eight grade students is 77. The design was classroom action research that carried out through inside outside circle with video technique in two cycles, on each cycle consisted of two sessions. The obtained data were collected by administering the instruments to the subjects, then qualitatively from the questionnaire. The result in each cycle showed that the pre-test was 65.5, than there was significant improvement in post-test 1 was 74.8, and last on post-test 2 was 82.7. It means that 75% of the subjects pass the passing grade. The result of the questionnaire showed that 99% of the students agree with implementation of this technique. In short, the present classroom action research showed that speaking skill of the eighth grade students of SMP Budi UtamaKerobokan in academic year 2019/2020 can be improved through inside outside circle with video.